The impact of liquidity on bank lending: Case of Tunisia - Mohamed Aymen Ben Moussa; Chedia Hedfi (The Institute of Academic Research and Publication (IARP), 2024)
Liquidity is the risk to a bank's earnings and capital arising from its inability to timely meet obligations when they come due without incurring unacceptable losses. Bank management must ensure that sufficient funds are available at a reasonable cost to meet potential demands from both fund providers and borrowers. Also, Lending is the process by which a financial institution provides funds to a borrower. Often called a lender, the institution typically receives interest in return for the loan. Lending in banking benefits lenders and borrowers alike by increasing liquidity within the marketplaces where loans are originated and used. This article aims to identify the impact of liquidity on bank lending. We used a sample of 12 banks in Tunisia over the period (2005….2022). By employing a method of panel static we found that liquidity has a significant impact on bank lending.